Social protection of civil servants in Europe : Report 68 - Onnée-Abbruciati, Marie-Laure; Fernandes, Christine; Hutsebaut, Martin (Brussels: European Trade Union Institute (ETUI), 2000)
"edited by Marie-Laure Onnée-Abbruciati, Christine Fernandes and Martin Hutsebaut"